De novo Transcriptome Analysis and Molecular Marker Development of Two Hemarthria Species - Huang, Xiu; Yan, Hai-Dong; Zhang, Xin-Quan; Zhang, Jian; Frazier, Taylor P.; Huang, De-Jun; Lu, Lu; Huang, Lin-Kai; Liu, Wei; Peng, Yan; Ma, Xiao; Yan, Yan-Hong (Frontiers in Plant Science, 2016)
Hemarthria R. Br. is an important genus of perennial forage grasses that is widely used in subtropical and tropical regions. Hemarthria grasses have made remarkable contributions to the development of animal husbandry and agro-ecosystem maintenance; however, there is currently a lack of comprehensive genomic data available for these species. In this study, we used Illumina high-throughput deep sequencing to characterize of two agriculturally important Hemarthria materials, H. compressa ‘Yaan’ and H. altissima ‘1110.’ Sequencing runs that used each of four normalized RNA samples from the leaves or roots of the two materials yielded more than 24 million high-quality reads. After de novo assembly, 137,142 and 77,150 unigenes were obtained for ‘Yaan’ and ‘1110’, respectively. In addition, a total of 86,731 ‘Yaan’ and 48,645 ‘1110’ unigenes were successfully annotated. After consolidating the unigenes for both materials, 42,646 high-quality SNPs were identified in 10,880 unigenes and 10,888 SSRs were identified in 8,330 unigenes. To validate the identified markers, high quality PCR primers were designed for both SNPs and SSRs. We randomly tested 16 of the SNP primers and 54 of the SSR primers and found that the majority of these primers successfully amplified the desired PCR product. In addition, high cross-species transferability (61.11%-87.04%) of SSR markers was achieved for four other Poaceae species. The amount of RNA sequencing data that was generated for these two Hemarthria species greatly increases the amount of genomic information available for Hemarthria and the SSR and SNP markers identified in this study will facilitate further advancements in genetic and molecular studies of the Hemarthria genus.